Antiarrhythmic and Hemodynamic Effects of Omega-3 Polyunsaturated Fatty Acids on Cardiovascular Diseases - A. N. Zakirova; N. E. Zakirova (Столичная издательская компания, 2022)
This review presents the results of previously performed epidemiological, experimental and clinical studies indicating the use of ω-3 PUFA (polyunsaturated fatty acids) contributes to reduce the risk of developing cardiovascular diseases. Experimental studies have shown ω-3 PUFA are exhibiting antiarrhythmic effects, improving endothelial function, showing an anti- inflammatory effect, affecting the rheological properties of blood, reducing triglyceride concentrations, and increasing the stability of atheromatous plaque. Wide-scale clinical trials have established high efficacy of ω-3 PUFA in primary and secondary prevention of coronary heart disease. It is found to reduce the risk of ventricular arrhythmias and sudden cardiac death. Also, reduces overall mortality and hospitalization rates due to cardiovascular causes in patients with chronic heart failure. Clinical efficacy among cardiovascular diseases of the prescription drugs ω-3 PUFA standardized by qualitative and quantitative compositions to be studied further in a comparison to the other medications with similar make-up.